2021
DOI: 10.1109/tnb.2020.3031202
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Idealization of Ion Channel Recordings – Open Channel Noise

Abstract: We propose a new model-free segmentation method for idealizing ion channel recordings. This method is designed to deal with heterogeneity of measurement errors. This in particular applies to open channel noise which, in general, is particularly difficult to cope with for model-free approaches. Our methodology is able to deal with lowpass filtered data which provides a further computational challenge. To this end we propose a multiresolution testing approach, combined with local deconvolution to resolve the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 49 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Within an HMM framework, one can only incompletely determine whether the data are compatible with the underlying model assumptions. Hence, despite the above described advantages, at least in simulations and real data examples in Pein et al (2021); Bartsch et al (2019), we observed that parameter estimates based on an idealization (either obtained by model-free approaches or by the Viterbi algorithm) appear to be more accurate than direct estimates by the Baum-Welch algorithm. Gating dynamics are time-continuous processes, but for simplification, many HMM approaches underlie a time-discrete Markov chain as an approximation.…”
Section: Hmm-based Analysismentioning
confidence: 72%
See 4 more Smart Citations
“…Within an HMM framework, one can only incompletely determine whether the data are compatible with the underlying model assumptions. Hence, despite the above described advantages, at least in simulations and real data examples in Pein et al (2021); Bartsch et al (2019), we observed that parameter estimates based on an idealization (either obtained by model-free approaches or by the Viterbi algorithm) appear to be more accurate than direct estimates by the Baum-Welch algorithm. Gating dynamics are time-continuous processes, but for simplification, many HMM approaches underlie a time-discrete Markov chain as an approximation.…”
Section: Hmm-based Analysismentioning
confidence: 72%
“…To decide whether the noise is heterogeneous, we recommend to more advanced users also the following systematic approach: if longer segments without gating events are present, one can use them to estimate the noise level. Alternatively, one can idealize the data with JSMURF or HILDE with heterogeneous noise setting and use the idealization to determine noise levels as detailed in (Pein et al 2021, Section VI-C).…”
Section: Choosing the Right Methodsmentioning
confidence: 99%
See 3 more Smart Citations